SOSIALISASI DAN PENERAPAN PERILAKU HIDUP BERSIH DAN SEHAT GUNA MEWUJUDKAN MASYARAKAT YANG PRODUKTIF DI DESA SEI KARANG - Surya Wardani,; Julianto Hutasuhut, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
PHBS stands for Clean and Healthy Behavior. While the notion of Clean and Healthy Living Behavior is a set of behaviors that are practiced on the basis of awareness as a result of learning that makes a person, family, group or community able to help themselves (independently) in the health sector and play an active role in realizing public health (Depkes RI, 2011). . PHBS can be carried out in various settings, namely at home, at school, at work, in public places, and in health institutions. This activity aims to educate and provide insightful knowledge to the community accompanied by practice to the Sei Karang village community about the importance of making efforts to live clean and healthy in daily life. This activity is one of the Independent Learning Programs for Students of the Muslim Nusantara University Al Washliyah, namely the KKNT Village Building Program which was carried out in Sei Karang Village, Galang District, Deli Serdang Regency. Clean and Healthy Lifestyle is basically an effort to transmit experiences regarding healthy living behavior through individuals, groups or the wider community by means of communication channels as a medium for sharing information. There are several steps that can be taken to support this activity, such as the coordination stage with partners, the preparation stage for counseling and training, the implementation stage for the extension and finally the evaluation stage in order to increase knowledge and improve related attitudes and behaviors.